1983
DOI: 10.3109/01485018308987576
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Plasma Zinc and Magnesium in Infertile Men

Abstract: Levels of zinc and magnesium were estimated in the seminal plasma of 83 men having various infertility problems. There was a wide overlapping of Zn and Mg mean values among the groups of normal and infertile men, a significant reduction in Mg mean value (but not Zn) only in the group with infection of the accessory genital glands, a very high positive correlation between Zn and Mg mean values in all groups, and a high positive correlation between either Zn or Mg and acid phosphatase (but neither fructose nor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Membranes of these organelles contain Mg 2ϩ -and Ca 2ϩ -dependent ATPase competitively inhibited by Zn 2ϩ (Ronquist et al, 1978a,b). High positive correlation between zinc and magnesium in seminal plasma has previously been reported (Papadimas et al, 1983;Umeyama et al, 1986), and in this study similar strong intercorrelations between all three cations were found (r ϭ 0.79-0.86, P Ͻ 0.01).…”
Section: Discussionsupporting
confidence: 72%
“…Membranes of these organelles contain Mg 2ϩ -and Ca 2ϩ -dependent ATPase competitively inhibited by Zn 2ϩ (Ronquist et al, 1978a,b). High positive correlation between zinc and magnesium in seminal plasma has previously been reported (Papadimas et al, 1983;Umeyama et al, 1986), and in this study similar strong intercorrelations between all three cations were found (r ϭ 0.79-0.86, P Ͻ 0.01).…”
Section: Discussionsupporting
confidence: 72%
“…A measurement of ''viscosity'' is frequently performed as recommended in the WHO Manual (1999), which defines an abnormal viscosity sample as one that can be drawn Arver and Sjoberg, 1982Fong et al, 1986Ford and Harrison, 1984Kilic et al, 1996Magnus et al, 1990Prien et al, 1990 Cl (mg/100 mL) 130 157 151.0 152 112 133 158 Gershbein and Thielen, 1988Hirsch et al, 1991Huggins and Johnson, 1933Huggins et al, 1942Jeyendran et al, 1989Kavanagh, 1985Rosecrans et al, 1987 K (mg/100 mL) 80 125 73.75 129 89.5 Bondani et al, 1973Gershbein and Thielen, 1988Girgis et al, 1980Hirsch et al, 1991Huggins et al, 1942 81.6 91 Jeyendran et al, 1989Kavanagh, 1985Mendiratta et al, 1980Nag and Chaudhuri, 1978Quinn et al, 1965; whole semen 88.0 113 50 126 154 Quinn et al, 1965;plasma Rosecrans et al, 1987Schirren, 1961Sheth and Rao, 1962aSheth and Rao, 196896 113.9 113 Skandhan et al, 1978Skandhan and Mazumdar, 1981Wood et al, 1982 Colleen et al, 1975Homonnai et al, 1978Jeyendran et al, 1989Kavanagh, 1985Papadimas et al, 1983 6.5 9.0 11.3 8.6…”
Section: Viscositymentioning
confidence: 99%
“…Abou-Shakra et al, 1989 Arver and Sjoberg, 1982Carpino and Siciliano, 1998Colleen et al, 1975Cooper et al, 199117.2 16.5 14 16 11.76 Hirsch et al, 1991Homonnai et al, 1978Jeyendran et al, 1989Kavanagh, 1985Lewis-Jones et al, 1996 8.4 14 15.0 Mandal and Bhattacharyya, 1986Mandal and Bhattacharyya, 1987aMandal and Bhattacharyya, 1990Mann and Lutwak-Mann, 1981Marmar et al, 1975; atomic absorption 18.9 13.4 9.26 19.0 16.6 Marmar et al, 1975; neutron activation Mawson and Fischer, 1956Mendiratta et al, 1980Papadimas et al, 1983Paz et al, 197714.64 14.7 69.29 10.6 19.5 Ponchietti et al, 1984Rosecrans et al, 1987Schoenfeld et al, 1979Sorensen et al, 1999Stankovic and Mikac-Devic, 197613 12.4 14.4 Stegmayr et al, 1982Umeyama et al, 1986Wood et al, 1982 Makler et al, 1981Mandal and Bhattacharyya, 1987bPolak and Daunter, 1984Velazquez et al, 1977 Purvis et al, 1986Rosecrans et al, 1987Schirren et al, 1977Schoenfeld et al, 1979225 302 136 Sheth and Rao, 1962bTauber et al, 1975…”
Section: Viscositymentioning
confidence: 99%
“…Some workers suggest the measurement of magnesium, rather than zinc, as markers for infection because it was found that seminal magnesium levels were markedly decreased during prostate infection. [16] In addition, reduced seminal magnesium is associated with increased thromboxane levels which may cause increase nitric oxide and vasoconstriction that results in premature ejaculation. [17] It is known that calcium is required to initiate the acrosome reaction with its attendant release of enzymes and membrane alterations needed for successful egg-sperm interaction.…”
Section: Introductionmentioning
confidence: 99%